2021
DOI: 10.13164/mendel.2021.2.074
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Neighborhood Size and Diversity Loss Rate in Particle Swarm Optimization With Ring Topology

Abstract: Measuring the population diversity in metaheuristics has become a common practice for adaptive approaches, aiming mainly to address the issue of premature convergence. Understanding the processes leading to a diversity loss in a metaheuristic algorithm is crucial for designing successful adaptive approaches. In this study, we focus on the relation of the neighborhood size and the rate of diversity loss in the Particle Swarm Optimization algorithm with local topology (also known as LPSO). We argue that the neig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It then exchanges information with its neighbors, considering both its own best position and the best position found by its neighbors. The particle’s velocity and position are updated using the information obtained from these local interactions [ 102 ]. In the ring topology, the updating equation for velocity and position remains the same as in the standard PSO algorithm.…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%
“…It then exchanges information with its neighbors, considering both its own best position and the best position found by its neighbors. The particle’s velocity and position are updated using the information obtained from these local interactions [ 102 ]. In the ring topology, the updating equation for velocity and position remains the same as in the standard PSO algorithm.…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%
“…It is important to note, that many optimizing liaisons (MOL) optimisation is based on the original particle swarm optimisation (PSO) [1,11,17]. Particle swarm optimisation (MOL) was invented and first applied by Marcus Pedersen [15].…”
Section: Many Optimizing Liaisons (Mol)mentioning
confidence: 99%
“…A new mutated genetic algorithm was employed to solve the problem of independent job scheduling in grid computing [51]. Study on the inner dynamics of PSO algorithm using network visualization showed the self-adaptive approaches of PSO [35]. The versatility of these algorithms had led to the development of hybrid algorithms.…”
Section: Introductionmentioning
confidence: 99%